Implementasi Metode Pembiasaan Berbasis Budaya Sekolah untuk Meningkatkan Karakter Religius Anak Berkebutuhan Khusus di SMPLB-PRI Pekalongan - Indri Agus Trianis (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2019)
This research is motivated by the results of preliminary observations in the Pekalongan SMPLB-PRI. Based on what researchers observed the uniqueness of children with special needs, then how their interactions with friends or the surrounding environment, whether the limitations and disadvantages of children with special needs have religious values. From the results of these preliminary observations the researcher took the title of implementing the culture-based habituation method of the school to improve the religious character of children with special needs in Pekalongan High School. The objectives of this study are: 1) To find out the implementation of a school culture-based habituation method to improve the religious character of Children with Special Needs at Pekalongan High School PRI. 2) To find out the obstacles encountered in implementing the culture-based customization method of schools to improve the religious character of Children with Special Needs in Pekalongan High School. This research is a qualitative research type of field research. Data collection methods using interviews, observation and documentation. The data analysis technique used the Miles and Huberman analysis method.